PARIETAL CONTRIBUTIONS TO LANGUAGE PROCESSING: PROGRESSIVE APHASIA IN POSTERIOR CORTICAL ATROPHY. (29th November 2012) - Crutch, S; Lehmann, M; Warrington, EK; Warren, JD; Rohrer, JD
Abstract : The role of the parietal lobes in human language processing remains unclear. Neurological studies focus upon the impact of atrophy to the anterior temporal lobe (semantic dementia), frontoinsular cortex (progressive non-fluent aphasia) and temporo-parietal junction (logopenic/phonological aphasia). We investigated the impact of neurodegeneration upon more posterior language areas by profiling language function in Posterior Cortical Atrophy (PCA). Fifteen patients with PCA, seven patients with logopenic/phonological aphasia (LPA) and 18 age-matched healthy participants completed linguistic tests evaluating auditory input processing, repetition and working memory, lexical and grammatical comprehension, single word retrieval and fluency, and spontaneous speech. Relative to healthy controls, PCA patients exhibited language impairments across all the domains examined, but with anomia, reduced phonemic fluency and slowed speech rate the most prominent deficits. PCA patients exhibited a milder dysphasic syndrome than LPA, with performance most similar on tests of auditory input processing, repetition and digit span, but relatively superior on tasks of comprehension and spontaneous speech (see figure 1B). In addition to the well-reported visual symptoms, PCA is characterised by a progressive dysphasia with prominent anomia and difficulty on phonologically-based tasks. Overlap in the linguistic profiles of PCA and LPA, which are both most commonly caused by Alzheimer's disease, emphasises the notion of a phenotypic continuum between typical and atypical manifestations of the disease.